Application of dynamic human resource management in the nursing management of a tertiary hospital (动态人力资源管理在某三级医院护理管理中的应用) - WANG Huaxin (王华新); TANG Ling (唐玲); E Haiyan (鄂海燕); LI Ye (李野); ZHAO Jialu (赵佳璐) (Association of Integrative Nursing, 2023)
Whether the allocation of nursing human resources is reasonable will directly affect the working attitude, work efficiency and work quality of employees. Reasonable and dynamic nurse human resource management is closely related to nursing quality and hospital benefits. This paper summarizes the application experience of dynamic human resource management in the nursing management. Guided by the dynamic management of nursing human resources, comprehensive training and reasonable nurse resources allocation were conducted to achieve the optimal use, allocation and service, alleviate the shortage of hospital nursing human resources, improve the emergency human allocation processing ability, improve the level of nursing management and improve the quality of nursing service. (护理人力资源的配置情况是否合理, 将会直接影响员工的工作态度、工作效率、工作质量, 合理及动态的护士人力资源管理与护理质量密切相关。本文总结了动态人力资源管理在医院护理管理中的应用经验, 通过护理人力资源的动态管理进行全方位的培训、合理调动护士资源, 达到最优使用、最优分配、最优服务, 进而缓解医院护理人力资源的不足, 提高应急人力调配处理能力, 提高护理管理水平, 提升护理服务质量。)